CDKL5 protein substitution therapy rescues neurological phenotypes of a mouse model of CDKL5 disorder. (20th February 2018) - Trazzi, Stefania; De Franceschi, Marianna; Fuchs, Claudia; Bastianini, Stefano; Viggiano, Rocchina; Lupori, Leonardo; Mazziotti, Raffaele; Medici, Giorgio; Lo Martire, Viviana; Ren, Elisa; Rimondini, Roberto; Zoccoli, Giovanna; et al.
Abstract: Cyclin-dependent kinase like-5 (CDKL5) disorder is a rare neurodevelopmental disease caused by mutations in the CDKL5 gene. The consequent misexpression of the CDKL5 protein in the nervous system leads to a severe phenotype characterized by intellectual disability, motor impairment, visual deficits and early-onset epilepsy. No therapy is available for CDKL5 disorder. It has been reported that a protein transduction domain (TAT) is able to deliver macromolecules into cells and even into the brain when fused to a given protein. We demonstrate that TAT-CDKL5 fusion protein is efficiently internalized by target cells and retains CDKL5 activity. Intracerebroventricular infusion of TAT-CDKL5 restored hippocampal development, hippocampus-dependent memory and breathing pattern in Cdkl5 -null mice. Notably, systemically administered TAT-CDKL5 protein passed the blood–brain-barrier, reached the CNS, and rescued various neuroanatomical and behavioral defects, including breathing pattern and visual responses. Our results suggest that CDKL5 protein therapy may be an effective clinical tool for the treatment of CDKL5 disorder.